Cold‐inducible promoter‐driven knockdown of Brachypodium antifreeze proteins confers freezing and phytopathogen susceptibility - Collin L. Juurakko; Melissa Bredow; George C. diCenzo; Virginia K. Walker (Plant Direct, 2022)
Abstract The model forage crop, Brachypodium distachyon, has a cluster of ice recrystallization inhibition (BdIRI) genes, which encode antifreeze proteins that function by adsorbing to ice crystals and inhibiting their growth. The genes were targeted for knockdown using a cold‐induced promoter from rice (prOsMYB1R35) to drive miRNA. The transgenic lines showed no apparent pleiotropic developmental defects but had reduced antifreeze activity as assessed by assays for ice‐recrystallization inhibition, thermal hysteresis, electrolyte leakage, and leaf infrared thermography. Strikingly, the number of cold‐acclimated transgenic plants that survived freezing at −8°C was reduced by half or killed entirely, depending on the line, compared with cold‐acclimated wild type plants. In addition, more leaf damage was apparent at subzero temperatures in knockdowns after infection with an ice nucleating pathogen, Pseudomonas syringae. Although antifreeze proteins have been studied for almost 60 years, this is the first unequivocal demonstration of their function by knockdown in any organism, and their dual contribution to freeze protection as well as pathogen susceptibility, independent of obvious developmental defects. These proteins are thus of potential interest in a wide range of biotechnological applications from cryopreservation, to frozen product additives, to the engineering of transgenic crops with enhanced pathogen and freezing tolerance.